2014
DOI: 10.7314/apjcp.2014.15.6.2571
|View full text |Cite
|
Sign up to set email alerts
|

The Exonuclease 1 Glu589Lys Gene Polymorphism and Cancer Susceptibility: Evidence Based on a Meta-analysis

Abstract: Background: Published studies on the association between the exonuclease 1 (EXO1) Glu589Lys polymorphism and cancer susceptibility have yielded conflicting results. Thus, a meta-analysis of published studies was performed to assess the possible association. Materials and Methods: All eligible case-control studies published up to January 2013 on the association between the EXO1 Glu589Lys polymorphism and cancer susceptibility were identified by searching PubMed, Web of Science, Science Direct and hand search. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
2
2
Order By: Relevance
“…Their conclusions could be considered to be inconsistent, which may be partially attributable to the relatively small sample size. The meta-analysis by Bayram 41 showed that the Glu589Lys polymorphism was not associated with overall cancer susceptibility, which contrasted with our own results. However, we found that the data reported by Bayram 41 from the studies by Wang et al 23 and Ibarrola-Villava et al 26 were not the same as the original data.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Their conclusions could be considered to be inconsistent, which may be partially attributable to the relatively small sample size. The meta-analysis by Bayram 41 showed that the Glu589Lys polymorphism was not associated with overall cancer susceptibility, which contrasted with our own results. However, we found that the data reported by Bayram 41 from the studies by Wang et al 23 and Ibarrola-Villava et al 26 were not the same as the original data.…”
Section: Discussioncontrasting
confidence: 99%
“…The meta-analysis by Bayram 41 showed that the Glu589Lys polymorphism was not associated with overall cancer susceptibility, which contrasted with our own results. However, we found that the data reported by Bayram 41 from the studies by Wang et al 23 and Ibarrola-Villava et al 26 were not the same as the original data. Another recent meta-analysis by Duan et al 42 concluded that the Glu589Lys polymorphism was significantly associated with increased cancer risk in all genetic models, which differed from our own results.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Exo1 knockout mice exhibit reduced survival, increased susceptibility to developing lymphomas (14), and sterility in both males and females (14). Defects in hExo1 are implicated in human cancers (15).…”
mentioning
confidence: 99%